How tryptophan levels in plant-based aquafeeds affect fish physiology, metabolism and proteome - Cerqueira, Marco (2021)
Fish meal replacement by plant-protein sources is a priority in aquaculture feeds. Within this framework, dietary supplementation with essential amino acids (EAA), as tryptophan (TRP), is strategic to ensure that the individual nutritional needs are met, besides promoting enhanced immunological status. The purpose of this study was to examine the beneficial effects of TRP incorporation in plant-protein source diets on fish growth performance and nutritional status. We tested diets with 20% lower (LTRP) and 27% higher (HTRP) of the putative requirements of TRP for seabream (Sparus aurata) and assessed its impact on fish physiology and liver metabolism and proteome. After 12 weeks, growth performance, body proximate, hepatic composition and liver metabolic profiling were similar between diets. Nevertheless, liver proteome analysis indicated a higher accumulation of proteins involved in acute-phase responses, typically triggered by infection, inflammation or trauma, in fish fed with HTRP diet as compared with those fed with LTRP. The overall results obtained suggest a potential beneficial effect of TRP supplementation in terms of immune stimulation, without compromising growth or feed intake. Moreover, proteomics and metabolic profiling demonstrate to be valuable tools in this endeavour. Significance: Nutritional needs are hard to assess in aquaculture fisheries, and many times controversial depending on the methodology employed. The estimated amino acid requirements depend on both fish species and stage development, making it extremely hard to standardise. On the other hand, the substitution of fish-based to plant-based protein sources diets towards a sustainable aquaculture, may imbalance these requirements, being necessary further studies to assess the impact on fish growth and development. Finally, the incorporation of crystalized amino acids such as TRP into diets aims global better performance both at fish health/immune condition and growth development. This work focused on the potential beneficial effects of TRP supplementation into diets with a plant-based protein source, addressing the effects on the liver metabolism and proteome, and on growth performance of Gilthead seabream juveniles, a species with special relevance and economical importance in the Mediterranean region. The present study by employing proteomics together with metabolic profiling shows that TRP supplementation at the tested doses, does not compromise growth performance, and seems to stimulate the immune system. Our findings can contribute to the development of new feed formulations for Gilthead seabream species, therefore, reinforcing the resilience and competitiveness of the on-growing aquaculture industry and impact directly the sustainability of living resources with the decrease of the fisheries needs to fulfil the human search for quality proteins consume.